GESTÃO DA COMUNICAÇÃO INTEGRADA: CONTRIBUIÇÕES PARA UMA ABORDAGEM SISTÊMICA Um estudo de caso da rede Magazine Luiza - Silva, Marília Saveri (2014)
This study investigates the course in the organizations, by a speculation about the three puts model (inputs, throughputs, outputs), that provides a systemic inter departmental vision that increases the interaction and awareness between the sections to achieve organizational objective goals. It represents characteristics and intersections between marketing, institutional and administrative communications. It also offers incidences in common between these concepts and reflects on the model of Three-dimensional integrated communication, when all of the actions of organizational communication converge, based on mission - vision - values trinomial and on 14 steps of Yanazes communication. Another analysis is verifying the theoretical assumptions from a case study in the Magazine Luiza enterprise, in order to explore how the concept of integrated communication has been grounded on the planning and the unity, based on the message of that organization. The methodology consists in bibliographic research, case study and an analysis about applied interviews. Along the results we have found, it was demonstrated that even in theoretical or empirical researches, that the systemic approach and the 3D Communication proposal, in fact, can offer some paths to an effective management of integrated communication.